2021
DOI: 10.3390/economies9040203
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Credit Standards on Aggregate Fluctuations in a Small Open Economy: The Role of Monetary Policy

Abstract: Empirical evidence demonstrates that credit standards, including lending margins and collateral requirements, move in a countercyclical direction. In this study, we construct a small open economy model with financial frictions to generate the countercyclical movement in credit standards. Our analysis demonstrates that countercyclical fluctuations in credit standards work as an amplifier of shocks to the economy. In particular, the existence of endogenous credit standards increases output volatility by 21%. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Conversely, in Tunisia, where the loan rate is indexed to the policy rate, the loan costs increase, impacting firms' net value. This mechanism, commonly referred to as the Fisher effect, exerts a detrimental influence on investment and real economic activities (Le 2021). Furthermore, we found that the bank's net worth decreased in response to monetary tightening.…”
Section: Restrictive Monetary Policymentioning
confidence: 66%
See 1 more Smart Citation
“…Conversely, in Tunisia, where the loan rate is indexed to the policy rate, the loan costs increase, impacting firms' net value. This mechanism, commonly referred to as the Fisher effect, exerts a detrimental influence on investment and real economic activities (Le 2021). Furthermore, we found that the bank's net worth decreased in response to monetary tightening.…”
Section: Restrictive Monetary Policymentioning
confidence: 66%
“…This shock was calibrated such that it determined a decrease in bank capital of 5% on impact. In this exercise, we used the bank leverage ratio as proxy of the measure of financial frictions, whereby the more the ratio increased, the more banks took risks (Suh and Walker 2016;Li 2022;Le 2021). Three cases were considered: a high level of financial frictions, ∅ b t = 15%; an average level of financial frictions, ∅ b t = 8.9%; and a low level of financial frictions, ∅ b t = 3%.…”
Section: Negative Bank Capital Shock and Conditions Of Low And High B...mentioning
confidence: 99%
“…In other words, the experiences gained at first can be considered to be changes in the effectiveness of monetary policy, but the fact is that the lack of attention to non-neoclassical channels has led to this. Recent studies show that different countries have seen different results from the impact of policies and monetary shocks on the real sectors of the economy due to the different characteristics of banks and firms, and factors such as the balance sheet and financial health of banks play a different role in the impact of monetary policy [10,59,62,64,[97][98][99][100].…”
Section: Introductionmentioning
confidence: 99%